(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
This article embarks on a comparative analysis of Yuri Bondarev’s «The hot snow» and Shukhrat’s «Years in overcoats». seminal novels that offer profound insights into the Soviet and Uzbek experiences of World War II. Employing a multidisciplinary approach that includes thematic analysis, narrative structure examination, and character development study, the research illuminates how these narratives navigate the themes of heroism, suffering, and moral dilemmas within the context of the war. By juxtaposing the distinct cultural and historical perspectives embedded in Russian and Uzbek literature, the study reveals both shared and unique aspects of the wartime experience, highlighting the complexity and diversity of World War II narratives. The analysis contributes to the fields of comparative literature and war studies, underscoring the significance of examining war literature from varied cultural viewpoints. It also identifies avenues for future research, particularly in the comparative study of Russian and Central Asian literary responses to the war. Ultimately, the article argues for the enduring value of World War II literature in fostering a more nuanced understanding of the conflict’s impact on humanity, emphasizing the role of literature in preserving memory and enriching our comprehension of the human condition amidst war.